2019
DOI: 10.7251/qol1901015a
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Indoor Air Quality of Akure, South – West, Nigeria

Abstract: Air quality has been a major concern throughout the world, Nigeria inclusive. The monitoring of air quality involves indoor and outdoor air quality. In this study, our concern was on indoor air quality. The aim of this study was to assess the air quality of residential homes (17), classrooms (3), hospitals (2), offi ces (5), Shops (2), and laboratories (5) in Akure, Nigeria in terms of formaldehyde (HCHO), total volatile organic compound (TVOC), Particulate matter (PM 1.0 ; PM 2.5 , and PM 10 ). A Multifunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
0
1
Order By: Relevance
“…The levels are 1-2 orders lower than the concentration of TVOC (1346-1466 μg/m 3 ) in Lagos slums (Okimiji et al, 2021) and in Abuja (660-9980 μg/m 3 ) (Wambebe and Duan, 2020). However, the mean indoor TVOC concentrations (3 and 362 μg/m 3 ) in Akure, Southwest Nigeria, is within the range for living rooms in this study (Abulude et al, 2019). The outdoor median TVOCs are significantly (p < 0.05) larger in the urban area than rural households by a factor of 2 during the dry and wet seasons.…”
Section: Voc Concentrationcontrasting
confidence: 56%
“…The levels are 1-2 orders lower than the concentration of TVOC (1346-1466 μg/m 3 ) in Lagos slums (Okimiji et al, 2021) and in Abuja (660-9980 μg/m 3 ) (Wambebe and Duan, 2020). However, the mean indoor TVOC concentrations (3 and 362 μg/m 3 ) in Akure, Southwest Nigeria, is within the range for living rooms in this study (Abulude et al, 2019). The outdoor median TVOCs are significantly (p < 0.05) larger in the urban area than rural households by a factor of 2 during the dry and wet seasons.…”
Section: Voc Concentrationcontrasting
confidence: 56%
“…Since students spend the majority of their time indoors and come into touch with classroom surfaces frequently, this is caused by crammed classrooms and the proximity of sources of release, such as waste dumps, which can lead to ingestion and inhalation [5]. As reported by Abulede et al [6] there are significant effects of weather on the pollutants, especially temperature. Another study by Oguntoke et al [7] revealed rural dwellers to be exposed to poor air quality with the concentrations of the five monitored gases significantly higher than the permissible limits.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the price, a cheap sensor will be helpful for detecting contaminants indoors. Research has been conducted indoors in locations with a variety of pollution sources [5,6], but few or no investigations have been conducted in locations where people smoke cigarettes. If one is being examined, it is not inappropriate.…”
Section: Introductionmentioning
confidence: 99%